E-Resources: A Reservoir for Information Seekers - V, Kalaiappan; S, Saravanan (International Journal of Information Studies, 2025)
E-Resources play an incredible role in knowledge development. It acts as a reservoir of academic pursuits. The modern generation scholars are highly depending on the electronic resources as it is more convenient and can be accessed at any point of time. E-Resources contains information pertaining to electronic journals, ebooks, teaching notes and slides. The paper explores the importance of e-resources in the medical field and considered four national institution of AYUSH as study. The study highlights that e-resources become an integral part of regular academic activity and the information seekers are getting the required information anywhere at any point of time.